Bipolar carbide-carbon high voltage aqueous lithium-ion capacitors. (February 2019) - Li, Jianmin; Kurra, Narendra; Seredych, Mykola; Meng, Xing; Wang, Hongzhi; Gogotsi, Yury
Abstract: MXenes - two-dimensional (2D) transition metal carbides and nitrides - are an emerging class of high rate pseudocapacitive materials due to their combination of fast surface redox reactions with metallic conductivity. The ability of MXenes to spontaneously intercalate aqueous cations, broadens the scope for developing metal-ion capacitors beyond the protic electrolytes. In this study, 2D titanium carbide (MXene) free-standing films are employed to evaluate the dependence of electrochemical performance in aqueous Li and Na-ion electrolytes. By contrast, high surface area porous nanoscale carbide derived carbon (nano-CDC) is employed as a surface electrosorbing electrode at anodic potentials. Both, 2D MXene and zero-dimensional (0D) nano-CDC, with contrasting charge storage mechanisms and complementary potential windows of operation, enable the construction of an aqueous Li-ion capacitor with a 2 V voltage window of operation. This asymmetric device shows high rate capability (71% retention from 10 to 1000 mV s −1 ) and good cycling stability with 99.3% retention after 10, 000 cycles. Furthermore, we demonstrate here the design of flexible bipolar carbide-carbon devices. Graphical abstract: Highlights: A titanium carbide (MXene)-porous carbide derived carbon based asymmetric aqueous Li-ion capacitor was fabricated. The widest operating voltage window of 2 V was achieved for MXene devices. The as assembled devices showed flexibility, ratability and long-term cycle stability. Bipolar carbide-carbon devices were demonstrated with optimal volumetric performance.